Performance analysis of a water-power combined system with air-heated humidification dehumidification process. (1st July 2017) - He, W.F.; Zhang, X.K.; Han, D.; Gao, L.
Abstract: Freshwater and power demand are necessary both for the life and production. This paper focus on the water-power combined system, in which the organic Rankine cycle (ORC) is integrated into the air-heated humidification dehumidification (HDH) desalination unit to satisfy the requirements of the freshwater and power coinstantaneously. Mathematical models of the energy balance within the HDH desalination and ORC power subsystem are presented, and the performance of the combined thermal system are demonstrated through numerical simulation. The calculated production of freshwater and power validate the practicability of the proposed combined platform. The simulation results show that peak values for the freshwater production, m ˙ p w = 19 . 53 kgh − 1, and gained output ratio (GOR) of the HDH desalination system, GOR = 2.82, are obtained at the balance case, while the maximum power of the ORC subsystem, W net = 6.04 kW, arises at m ˙ s w / m ˙ d a = 9 . Furthermore, the maximum value of η WPCS = 94.86% is also obtained at the balance case. It is also illustrated that the elevation of the terminal temperature difference is effective to raise the generated power from the ORC subsystem although the final energy utilization efficiency will be influenced, and the maximum power output is raised from W net = 3.33 kW to W net = 8.17 kW while the relevant peak value of the total thermal efficiency, η WPCS decreases from η WPCS = 109.79% to η WPCS = 86.89% with the increasing of the terminal temperature difference from Δ T e = 10 K to Δ T e = 20 K. The trend of the freshwater and power variation laws imply that the mass flow rate ratio should be determined according to the actual water and power demand during the design period. Highlights: A water-power combined system (WPCS) is proposed. Mathematical models of the WPCS are presented. Performance of the combined thermal system are demonstrated. Influence from the terminal temperature difference is investigated.